Efficient call admission control for heterogeneous services inwireless mobile ATM networks. - Zhao, Dongmei (IEEE Communications magazine)
An efficient call admission control scheme for handling heterogeneous services in wireless ATM networks is proposed. Quality-of-service provisioning of jitter bounds for constant bit rate traffic and delay bounds for variable bit rate traffic is used in the CAC scheme to guarantee predefined QoS levels for all traffic classes. To reduce the forced handoff call dropping rate, the CAC scheme gives handoff calls a higher priority than new calls by reserving an appropriate amount of resources for potential handoff calls. Resource reservation in the CAC scheme makes use of user mobility information to ensure efficient resource utilization. Simulation results show that the proposed CAC scheme can achieve both low handoff call dropping rate and high resource utilization